Legal provisions for the depositary bank in the cash deposit contract according to Yemeni law: A comparative study - Al-Shaddadi, Hussein Ahmed Saleh (Journal of Economic, Administrative and Legal Sciences, 2025)
Upon the completion of the cash deposit contract between the depositing customer and the depositary bank, a number of legal effects result, represented by a number of mutual rights and obligations between its parties. Yemeni Commercial Law No. (32) of 1991 AD organized the cash deposit contract and clarified the legal provisions for the depositary bank and its obligations and rights in this contract. However, in late 2016, Yemeni commercial banks operating in Yemen stopped returning cash deposits to their depositors. And until now, these witnesses and witnesses are still a problem that benefits from research and study in the folds of the Yemeni legal texts that organize the obligations of the depositary bank and its rights in the depositary contract in a good way and a statement of comparative law. Especially since the depositary bank is bound by a number of contractual obligations, the most important of which is its obligation to return the deposit to the depositor customer upon request or upon the due date for its recovery or upon the fulfillment of the contractual conditions stipulated in the deposit contract, in addition to the fact that this obligation is legal according to the text of Article (358) of the Yemeni Commercial Law. In order to cover all the legal and jurisprudential aspects of the legal provisions of the depositary bank in the cash deposit contract, this required following a mixed descriptive, analytical and comparative approach in explaining the obligations of the depositary bank and its acquired rights in the deposit contract. In this study, we have reached a number of results, the most important of which is the absence of a banking legal system in Yemen, which requires the legal legislator to move to reconsider the organization of the legal provisions regulating commercial banks in the cash deposit contract, considering it one of the most important banking contracts that other banking legal legislations do not lack reference to and the organization of legal aspects related and connected to it. Not only that, but it has become necessary to issue a unified banking law that regulates banking work in Yemen, ensuring the removal of conflict and contradiction between the scattered texts and ensuring that commercial banks fulfill their obligation to return cash deposits to depositors.